PENGENDALIAN HIPERTENSI MELALUI PEMERIKSAAN KESEHATAN DAN TERAPI RENDAM KAKI MENGGUNAKAN AIR HANGAT DI NAGARI BALAH AIA SUNGAI SARIK KABUPATEN PADANG PARIAMAN - Mariza Elvira (Stikes Syedza Saintika Padang, 2023)
Hypertension is a chronic increase in blood pressure, where the systolic pressure is above 140 mmHg and the diastolic pressure is above 90 mmHg. Based on the results of basic health research, the prevalence of hypertension in West Sumatra was 25.6% with a total of 176,169 cases detected by measuring blood pressure. In Padang Pariaman there are as many as 22% of cases of hypertension. Based on the data obtained, hypertension is the second most common disease in the working area of the Sungai Sariak Public Health Center with a total of 325 cases. The purpose of this community service activity is to check blood pressure and soak feet using warm water for people with hypertension so that people who have a history of hypertension can control blood pressure. Methods of implementation in the form of checking blood pressure, doing foot soaks using warm water, leaflets, discussions and questions and answers. The results of the activity were obtained from 36 people who took part in blood pressure checks, 25 of whom had a history of hypertension, after soaking their feet using warm water 14 people experienced a decrease in their blood pressure. Hypertension control is not yet maximal in people who have a history of hypertension because people still rarely check blood pressure, still consume foods that can trigger a recurrence of hypertension, are lazy to go to health services, it is necessary to carry out routine health checks and provide education as a form of effort to control hypertension. Keywords : Hypertension ; foot soak